Metamorphoses of ethnocultural identity in the modern urban environment - Kurbacheva, Olga V. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
This article examines the characteristics of creating an ethnocultural identity in modern urban settings. The author notes trends in the actualisation of ethnocultural identity while accounting for the population’s numerical and age indicators, and the existence of an aggravating sociodynamic external element. The research focuses in particular on highlighting problematic elements of immigrant ethnic self-categorisation: ethnic culture transforms into a symbolic story and a means of self-presentation in a new ethnocultural setting. The status and importance of ethnocultural identity in the daily urban environment of ethnophores is another issue that the author brings up. The preservation of local identity and intragroup cohesiveness emphasises the institutional and individual formats for discussing ethnicity. It is stressed that in order to understand ethnicity, one must adopt the constructivist paradigm, which views ethnicity as a ﬂexible and open structure whose membership is mostly decided by symbolic markers rather than objective markers.
Keywords: ethnos; ethnicity; ethnocultural identity; city; metropolis; migration; migrant; ethnophor; tolerance; ethnic stereotypes; dialogue of cultures; constructivism